2017
DOI: 10.1007/s11409-017-9178-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and socio-emotional interactions in a positive and a negative group climate

Abstract: The ability to collaborate has been identified as an essential learning outcome for the 21 st century. However, if group members lack the skills, abilities, and attitudes to work in a team, these groups may work inefficiently or fail to achieve what they set out to do. To achieve success, group members need to engage in productive regulatory processes to manage cognitions, behaviors, motivation, and emotions as needed to attain desired outcomes. One area of regulation that has been underemphasized in collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(141 citation statements)
references
References 136 publications
7
112
0
11
Order By: Relevance
“…The results of the current study suggest that socio-emotional support was more often incorporated into the very moments with regulation in social interaction than without. The result is in line with recent studies that have explored how aspects of regulation in social interaction, such as monitoring challenges, may intertwine socio-emotional interaction, such as encouragement (Lajoie et al, 2015;Bakhtiar et al, 2018). However, though previous studies have noted humor as a part of positive socio-emotional interaction during moments with regulation in social interaction (e.g., Isohätälä et al, 2017;Volet, Summers, et al, 2009), the current study did not indicate an increased frequency of humor in episodes with regulation in social interaction.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the current study suggest that socio-emotional support was more often incorporated into the very moments with regulation in social interaction than without. The result is in line with recent studies that have explored how aspects of regulation in social interaction, such as monitoring challenges, may intertwine socio-emotional interaction, such as encouragement (Lajoie et al, 2015;Bakhtiar et al, 2018). However, though previous studies have noted humor as a part of positive socio-emotional interaction during moments with regulation in social interaction (e.g., Isohätälä et al, 2017;Volet, Summers, et al, 2009), the current study did not indicate an increased frequency of humor in episodes with regulation in social interaction.…”
Section: Discussionsupporting
confidence: 91%
“…Järvelä, Järvenoja, Malmberg, Isohätälä, and Sobocinski (2016) found that socio-emotional interaction (i.e., interaction about positive or negative emotions or motivation; increasing or decreasing group cohesion, inducing laughter) was often involved in the planning phase of group work when learners activated beliefs and processes in preparation for the learning. Recently, Bakhtiar et al (2018) illustrated the interplay between regulatory processes and socio-emotional interactions, suggesting that a positive climate group frequently incorporated positive socio-emotional interactions, such as encouraging participation and motivation, in regulating their learning. These findings imply that joint and positive interaction and regulation in social interaction may converge in social interaction.…”
Section: Regulation and Joint Positive Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined, this evidence showcases the significance of social dynamics in productive collaboration. In this study, social dynamics are understood as the sustained pattern of shared emotions and social behaviors that lead to a group's climate of a given valence‐positive versus negative, and that influences patterns of participation (Bakhtiar, Webster, & Hadwin, ).…”
Section: A Tridimensional Model Of Productive Collaborationmentioning
confidence: 99%
“…To study motivation and emotion regulation as a multi-layered phenomenon and as a part of the learning process, however, presumes going beyond recognising and capturing the subjective interpretations and explanations or focusing solely on the process data. As we have argued above, the process in which the effects of motivational and emotional conditions actualise into products of learning and motivation regulation are composed of both individual beliefs and processes taking place in the situation (Bakhtiar, Webster, & Hadwin, 2018). Subjective data (e.g., repeated and contextualised self-reports) can reveal students' intentions to learn and the type of beliefs they have about themselves as learners (McCardle & Hadwin, 2015).…”
Section: Claim: Motivation and Emotion Regulation Is Influenced By Thmentioning
confidence: 99%